Process Optimization of Cumene Production: Energy Efficiency Optimization and Conversion Enhancement through Heat Integration and Recycle Strategies - Farrel Dzakwan Alghiffary; Alfandi Maulana Gempa; Nabiel Athallah Ayyubi Nugroho; Juan R. Syahid; Otniel Galih Rajendra (Journal of Chemical Engineering Research Progress, 2026)
Cumene production via benzene–propylene alkylation is a highly exothermic process that requires effective thermal management. This study aims to optimize energy efficiency and enhance conversion performance in cumene production through the integration of reactor heat recovery and recycle strategies. To improve heat utilization efficiency, the process was modified by integrating a circulating heat transfer fluid system that captures reactor heat and reuses it for feed preheating, thereby reducing external utility demand. Additional heat released during effluent cooling is recovered to supply the mechanical energy required for pumping. The modified and baseline configurations were modeled using chemical process simulator and evaluated using a net energy (NE) framework. Results show that the basic process yields an NE of 3,119,682.58 kJ/h, while the modified process achieves 2,055,114.79 kJ/h, with 21,294,605.8 kJ/h of internal energy successfully recovered and reused. This demonstrates a substantial improvement in thermal integration and reduced reliance on external heating. Furthermore, the introduction of a vapor phase benzene recycle stream enhances benzene conversion, suppresses secondary alkylation, and increases cumene yield. Overall, the integrated heat recovery and recycle strategy significantly improves energy efficiency, conversion performance, and sustainability in cumene production. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).